Incidence of social resistance in provincial mining legislation. The cases of Córdoba and Catamarca (2003-2008) - Christel, Lucas (2013)
During the last decade in Argentina, the growth of open pit mining has faced strong social resistance and provincial laws prohibiting such activity. This work aims to analyse the ways in which the different subnational political regimes and economic systems impact upon the possibility of incidence of social resistance on provincial mining legislation, looking at the cases of Cordoba and Catamarca.